Inventarisasi Jenis-jenis Tanaman Pekarangan dan Pemanfaatannya di Desa Tanjung Merpati Kecamatan Kembayan Kabupaten Sanggau - Rafdinal, Ulul Maulina Riami Elvi Rusmiyanto PW (Jurnal Protobiont, 2019)
The yard is a plot of land located directly around the house of residence with clear boundaries, planted with one or various type of plants and still have ownership as well as functional relationship with the house concerned. This aims of this study to determine the species of yard plants and their use in Tanjung Merpati Village, Kembayan sub-district, Sanggau districts. The study was conducted from March to May 2017. Location determinations of the study was carried out by purposive random sampling methode which is based on the yard area category, namely large, medium and small categories. Acording to the research finding, there are 89 species of plants belonging to 4 Classes, 34 Orders, and 55 Families. The four classes of plants found were Magnoliopsida, Liliopsida, Gnetopsida and Cycadopsida. Based on the utilization of yard plants found in Tanjung Merpati Village, those plants are dividedÂ  into 5 groups, namely ornamental plants, fruit plants, vegetable, medicinal plants and herbs.